2017
DOI: 10.1039/c6ay03089k
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive detection of Cr(vi) in groundwater by bimetallic NiFe nanoparticles

Abstract: Hexavalent chromium (Cr(vi)) is one of the most toxic heavy metal pollutants in groundwater, and thus the detection of Cr(vi) with high sensitivity, accuracy, and simplicity and low cost is of great importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The detailed TEM images clearly show the double-layered CS structure on the Cu NA substrate: the inner electrodeposited metallic NiFe 0.10 Cr 0.10 layer with a thickness of 50–70 nm and the outer activated hydroxide layer with a thickness of 10–30 nm (Figure c,d). A series of diffraction rings are presented in the selected area electron diffraction (SAED) pattern, which can be indexed to {111}, {200} planes of NiFe alloy and {110}, {201}, {113} planes of β-Ni­(OH) 2 (Figure f). Similar diffraction rings can be observed in the SAED pattern of CS-NiFe 0.10 , with a slight increase of the lattice space of the {110}, {113} planes of β-Ni­(OH) 2 (Figure S6). This slight change in lattice space can be attributed to incorporation of Cr with a smaller atomic radius into the β-Ni­(OH) 2 crystal.…”
mentioning
confidence: 59%
“…The detailed TEM images clearly show the double-layered CS structure on the Cu NA substrate: the inner electrodeposited metallic NiFe 0.10 Cr 0.10 layer with a thickness of 50–70 nm and the outer activated hydroxide layer with a thickness of 10–30 nm (Figure c,d). A series of diffraction rings are presented in the selected area electron diffraction (SAED) pattern, which can be indexed to {111}, {200} planes of NiFe alloy and {110}, {201}, {113} planes of β-Ni­(OH) 2 (Figure f). Similar diffraction rings can be observed in the SAED pattern of CS-NiFe 0.10 , with a slight increase of the lattice space of the {110}, {113} planes of β-Ni­(OH) 2 (Figure S6). This slight change in lattice space can be attributed to incorporation of Cr with a smaller atomic radius into the β-Ni­(OH) 2 crystal.…”
mentioning
confidence: 59%
“…Several combinations of nanomaterials have been investigated for improving the performance of the sensors [ 27 , 56 , 57 ]. The incorporation of nanocomposites as sensing material affords various advantages including, high selectivity, high surface area and fast electron-transfer rate of the electroactive species to electrode surface [ 58 , 59 , 60 , 61 , 62 ]. Moreover, those nanocomposites provide high electrical conductivity thanks to the synergistic effect which is rarely explained in the literature.…”
Section: Electrochemical Sensors For Hexavalent Chromium Determinamentioning
confidence: 99%
“…Weidong Kang et al [ 59 ] reported a new amperometric sensor based on NiFE bimetallic nanoparticles for sensitive detection of Cr(VI) in groundwater with good recovery of 98–104%. The NiFE possessed multiple oxidation states which make the surface very active.…”
Section: Electrochemical Sensors For Hexavalent Chromium Determinamentioning
confidence: 99%
“…Although these contaminants have not been discharged into groundwater directly, they can permeate into groundwater due to their strong mobility. Many studies have shown that nitrate and chrome concentrations in groundwater are higher than the ambient levels [3,11]. Several methods have been used for the simultaneous removal of nitrate and hexavalent chromium from groundwater and soils, including biofilm reactors [12], membrane reactors [13], phytoremediation [14], three-dimensional electrocatalytic reactors [15] and bio-electrochemical systems [16].…”
Section: Introductionmentioning
confidence: 99%